Forum Acusticum 1996 – The 1st Convention of the European Acoustics Associaction EAA Antwerpen, Belgium 1-4 April 1996 - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1995)
FORUM ACUSTICUM 1996, the first Convention of the European Acoustics Association EAA-EEIG, is to be held on the campus of the University of Antwerpia, U.I.A. Belgium from 1 to 4 April, 1996. In order to ensure a high quality convention and a large number of participants, a number of EAA Societies merge their national meetings into the European Convention. One of the main goals of this convention will be to foster scientific and cultural exchanges, especially among the young acousticians. EAA is in charge of the overhead organization. The convention is organized by the Belgian Acoustical Association ABAV and the Technological Institute of the Royal Flemish Society of Engineers TI-K VIV.